Pandangan Ideologis-Teologis Muhammadiyah dan Majlis Tafsir Al-Qur’an - Mustolehudin Mustolehudin (Analisa: Journal of Social Science and Religion, 2014)
Abstract The dynamics of the religious life relation in Surakarta since the rolling of reformation isinteresting to observe. Social-religious history in Surakarta is grows and develops throughlong-term process, one of them was the birth of Islamic purification movement that has beendoing initiated by Muhammadiyah and MTA.This Research usesqualitative-descriptive method. The research aim to understandthe pattern of relation between Muhammadiyah and MTA, the pattern of cooperationand dispute and factors influenced them in composing the harmony of religious life inSurakarta. Research result showed that relation between them is tend to bepersonalrelation. The similarity of relationship between them is theological-ideological relationship,which is Islamic purification credo. In axiological term both refuse the practice of takhayul,bid’ah and khurafat (TBC). Basic differences between these two different institutions are;first, Muhammadiyah is more open (inclusive), whereas MTA is more closed (exclusive).Second, learning method which Muhammadiyah applies is indoctrination, MTA is moredoctrinatian . Third, the leadership sector in Muhammadiyah is organizational, while MTAis imamah model. Fourth, the conflict between both of them is happens because of migrationof Muhammadiyah pilgrims to MTA, however this conflict does not reach the level of massconflict, because hey carry the same vision, Islamic purification movement.Keywords : Relation, Cooperation, Conflict, Purification, Muhammadiyah, MTA. AbstrakGerakan sosial keagamaan di Surakarta, tumubuh dan berkembang sesuai dengan zamankondisi sejarah yang terjadi. Muhammadiyah dan MTA merupakan salah satu contohorganisasi sosial keagamaan yang melakukan gerakan pemurnian Islam di Surakarta.Penelitian ini dilakukan untuk mengetahui relasi antara Muhammadiyah dan MTA,dan bagaimana relasi dan kontestasi antar keduanya. Dengan menggunakan metodekualitatif, hasil penelitian menunjukkan bahwa hubungan yang dibangun antar keduanyacenderung bersifat personal. Kesamaan hubungan antar keduanya lebih cenderung kepadahubungan ideologis-teologis, yakni kredo pemurnian Islam. Secara aksiologis keduanyamenolak praktek takhayul, bid’ah dan khurafat (TBC). Perbedaan mendasar antara kedualembaga keagamaan tersebut adalah; Pertama, Muhammadiyah lebih terbuka (inklusif),sedangkan MTA cenderung tertutup (eksklusif). Kedua, metode pengajaran yang dilakukanMuhammadiyah bersifat indoktrinasi, MTA lebih doktrinasi. Ketiga, dalam bidangkepemimpinan Muhammadiyah dipilih secara organisasional, sedangkan MTA dipilih dengan model imamah. Keempat, pertentangan antar keduanya terjadi karena adanyamigrasi jamaah Muhammadiyah ke MTA, namun hal ini tidak sampai menimbulkankonflik massa, karena keduanya mengusung gerakan yang sama yaitu pemurnian Islam.Kata kunci: Purifikasi, Ideologi, Teologi, Muhammadiyah, MTA.